Banking system stability: a cross-Atlantic perspective - Philipp Hartmann; Stefan Straetmans; Casper de Vries (European Central Bank (ECB), 2005)
This paper derives indicators of the severity and structure of banking system risk from asymptotic interdependencies between banks' equity prices. We use new tools available from multivariate extreme value theory to estimate individual banks' exposure to each other (“contagion risk”) and to systematic risk. By applying structural break tests to those measures we study whether capital markets indicate changes in the importance of systemic risk over time. Using data for the United States and the euro area, we can also compare banking system stability between the two largest economies in the world. For Europe we assess the relative importance of cross-border bank spillovers as compared to domestic bank spillovers. The results suggest, inter alia, that systemic risk in the US is higher than in the euro area, mainly as cross-border risks are still relatively mild in Europe. On both sides of the Atlantic systemic risk has increased during the 1990s.
Keywords: C49; F36; G21; 330; asymptotic dependence; banking; Multivariate Extreme Value Theory; Structural Change Tests; systemic risk; Bank; Kreditrisiko; Risikomanagement; EU-Staaten; USA